OPTIMASI FORMULA TABLET EFFERVESCENT EKSTRAK RIMPANG JAHE MERAH (Zingiber officinale Roxb. Var rubrum) - Henny Dwi Arini; Lannie Hadisoewignyo (Universitas Sanata Dharma, 2012)
Abstract:This study aims to determine the effect of sodium citrate and fumaric acid as a source of acid in the tablet formula effervescent red ginger rhizome extract (Zingiber officinale Roxb. var rubrum) and obtain the optimum composition of the formula that has the physical properties of tablet effervescent red ginger rhizome extract (Zingiber officinale Roxb. var rubrum) that meet the requirements. Optimization techniques used in research is a method of factorial design with two factors and two levels of sodium citrate and fumaric acid with low levels of 80 mg, and high levels of 120 mg. Responses were observed to obtain optimum formula is hardness, friability, and the soluble tablet (effervescent time). The result is the concentration of sodium citrate and fumaric acid did not significantly affect tablet hardness effervescent. Meanwhile, that is significantly influences the friability and time effervescent soluble tablets. However, the interaction between sodium citrate and fumaric acid did not significantly affect the hardness, friability, and the soluble tablet effervescent red giinger extract. Optimum formula tablets obtained effervescent namely sodium citrate 80 mg and 80 mg of fumaric acid with 6,529 kgf response tablet hardness, tablet friability 0,1354%, and effervescent time of 5,98 minutes. Key words : Red ginger, effervescent tablet, factorial design